2019
DOI: 10.3389/fpsyg.2019.00645
|View full text |Cite
|
Sign up to set email alerts
|

Varimax Rotation Based on Gradient Projection Is a Feasible Alternative to SPSS

Abstract: Gradient projection rotation (GPR) is an openly available and promising tool for factor and component rotation. We compare GPR toward the Varimax criterion in principal component analysis to the built-in Varimax procedure in SPSS. In a simulation study, we tested whether GPR-Varimax yielded multiple local solutions by creating population simple structure with a single optimum and with two optima, a global and a local one (double-optimum condition). The other conditions comprised the number of components ( … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Six items were from the knowledge domain mathematics and six items were from the knowledge domain of economics. Two PCA components, two MFA factors, and two SPFA factors were Varimax-rotated by means of the gradient projection method provided by Bernaards and Jennrich (2005) based on the R-script of Weide and Beauducel (2019). The empirical correlations and the script of PCA, MFA, and SPFA combined with GPR-Varimax rotation are available in the Supplementary Material (section 2).…”
Section: Resultsmentioning
confidence: 99%
“…Six items were from the knowledge domain mathematics and six items were from the knowledge domain of economics. Two PCA components, two MFA factors, and two SPFA factors were Varimax-rotated by means of the gradient projection method provided by Bernaards and Jennrich (2005) based on the R-script of Weide and Beauducel (2019). The empirical correlations and the script of PCA, MFA, and SPFA combined with GPR-Varimax rotation are available in the Supplementary Material (section 2).…”
Section: Resultsmentioning
confidence: 99%
“…Two additional analyses were reported for the l = .50 ( n = 400, 1,000) condition of the orthogonal population models to investigate the robustness of the results of the overall simulation study. It has been shown that a number of different starting solutions might improve the performance of the gradient projection algorithm for factor rotation (Weide & Beauducel, 2019). As random starts need a substantial amount of computation time, an additional simulation was performed with only 200 runs for 10 conditions: The orthogonal population models with 2 + 2, 3 + 3, 4 + 4, 5 + 5, and 6 + 6 factors (= 5 population models × 2 sample sizes) to compare the sample average M (c) for 20 random start solutions with the sample average M (c) reached with a single start solution in the overall simulation.…”
Section: Methodsmentioning
confidence: 99%
“…It is therefore not surprising that simulation studies for the evaluation of methods of factor rotation were typically also based on simple structure models with salient loadings of each variable on only one factor (Velicer & Jackson, 1990). Although degraded simple structures with some substantial secondary loadings have sometimes been investigated (Schmitt & Sass, 2011; Weide & Beauducel, 2019) these degraded structures did not correspond to a faceted loading pattern. Since Guilford (1967) used target rotation, Jäger (1982) used a priori task aggregates, and simulation studies used only degraded simple structures one can conclude that population loading patterns representing more than one facet have not been explored systematically by means of EFA and subsequent (purely) explorative rotation toward simple structure.…”
Section: An Approach For Efamentioning
confidence: 99%
“…Important metrics were selected using an evaluation of the degree of redundancy based on a correlation matrix ( Riitters et al., 1995 ). Factors are subjected to varimax rotation to determine loading factors, and components that have an eigenvalue of >1 are retained ( Weide and Beauducel, 2019 ). Following data normality test, Spearman's product moment correlation between selected landscape metrics is used.…”
Section: Methodsmentioning
confidence: 99%